Electronic structure and bonding of small Pd clusters on stoichiometric and reduced SnO2(110) surfaces - Robina, A. (2014)
In the present work, we have studied the interaction of palladium adsorbed on SnO2 (110) surfaces, considering the possible formation of clusters on the surface using density functional theory (DFT) calculations. We report structure, adsorption, and bonding properties of Pdn (n = 1–5) on stoichiometric and reduced SnO2 (110) surfaces. Although palladium can be adsorbed as metal clusters on both types of surfaces, these clusters can be more easily decomposed into Pd atoms on the reduced SnO2 surface. Pd interacts mainly with bridging O atoms on stoichiometric surfaces while it bonds strongly with Sn on the reduced surface.